Interplay Between Geometry and Spin Dynamics in Elongated Magnetic Nanoislands: Elliptical Vs Stadium-Shaped Cases - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2025)
Through numerical simulations, we investigate the equilibrium states and dynamic responses of stadium-shaped and elliptical nanodots in the absence of a bias field. Our findings reveal two distinct equilibrium states – single domain and vortex – identified in these nanodots. Notably, the resonant frequencies and the number of peaks in the dynamics response are shown to be influenced by the minimum energy configuration, which is intricately linked to the system s aspect ratio. The insights gained from this exploration contribute to a deeper understanding of the interplay between geometric parameters and dynamic behavior in low-dimensional magnetic nanostructures, offering valuable considerations for the design and optimization of on-chip microwave devices in spintronics and magnonics applications. © 2025 Elsevier B.V.